Seawater-corrosion-resistant ultrafiltration membrane for water treatment and preparation method thereof

By preparing seawater-resistant ultrafiltration membranes and utilizing a combination of specific material components, the problems of easy corrosion and fouling of traditional ultrafiltration membranes in seawater treatment have been solved, achieving highly efficient seawater treatment results.

CN121060338APending Publication Date: 2025-12-05ZHONGSHENGYUAN (HAINAN) ECOLOGICAL ENVIRONMENT DEV CO LTD

Patent Information

Application Number
CN202511173332.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-21
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Traditional ultrafiltration membranes are susceptible to corrosion and fouling in seawater treatment, leading to performance degradation and increased water treatment costs and operational difficulties.

Method used

The ultrafiltration membrane is formed by mixing and coating a mixture of carboxyl-containing fluorinated polyarylether sulfone material, quaternized zinc-based metal-organic framework material, modified molybdenum disulfide nanopowder, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent and sodium dodecyl sulfate, and other components to form a membrane with good chemical stability, antibacterial properties and photocatalytic ability.

Benefits of technology

Ultrafiltration membranes exhibit excellent corrosion resistance and antifouling ability in seawater environments, extending service life, improving removal performance, reducing cleaning frequency and operating costs, and enhancing self-cleaning ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121060338A_ABST
    Figure CN121060338A_ABST
Patent Text Reader

Abstract

The invention relates to the field of ultrafiltration membranes, in particular to a seawater-corrosion-resistant ultrafiltration membrane for water treatment and a preparation method of the seawater-corrosion-resistant ultrafiltration membrane, which are used for solving the problems that the conventional ultrafiltration membrane is easily corroded and polluted in a seawater water treatment environment, so that the performance of the ultrafiltration membrane is remarkably reduced, and the water treatment cost and the operation difficulty are increased. The ultra-filtration membrane takes a carboxyl fluorine-containing polyarylether sulfone material as a main raw material, so that the ultra-filtration membrane has good chemical stability and corrosion resistance in a seawater environment, a quaternized zinc-based metal organic framework material is added into the ultra-filtration membrane, and a porous structure of the quaternized zinc-based metal organic framework material is utilized to enable the ultra-filtration membrane to have higher permeability, so that the removal performance of the ultra-filtration membrane is improved; meanwhile, the ultra-filtration membrane can be endowed with excellent antibacterial performance, formation of a biological membrane is effectively inhibited, biological pollution is avoided, the self-cleaning and anti-pollution capacity of the ultra-filtration membrane can be improved by adding the modified nano molybdenum disulfide powder, the removal performance of the ultra-filtration membrane is guaranteed for a long time, and the water treatment effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the field of ultrafiltration membranes, in particular to a seawater corrosion-resistant ultrafiltration membrane for water treatment and a preparation method thereof. BACKGROUND

[0002] As an important membrane separation technology, the ultrafiltration membrane has been widely applied in the field of water treatment. However, in the seawater treatment environment, the traditional ultrafiltration membrane is easily corroded and polluted due to the large amount of chloride ions, salt, microorganisms, algae and organic pollutants in seawater, and the performance of the ultrafiltration membrane is significantly reduced, thereby increasing the water treatment cost and operation difficulty.

[0003] Therefore, it is of great practical significance to develop a seawater corrosion-resistant ultrafiltration membrane for water treatment and a preparation method thereof. SUMMARY

[0004] In order to overcome the above technical problems, the purpose of the application is to provide a seawater corrosion-resistant ultrafiltration membrane for water treatment and a preparation method thereof, which solves the problem that the existing traditional ultrafiltration membrane is easily corroded and polluted in the seawater treatment environment, the performance of the ultrafiltration membrane is significantly reduced, and the water treatment cost and operation difficulty are increased.

[0005] The purpose of the application can be achieved by the following technical solutions.

[0006] In a first aspect, the application provides a seawater corrosion-resistant ultrafiltration membrane for water treatment, comprising the following components by weight:

[0007] 17-25 parts of carboxyl-containing fluorine polyarylether sulfone material, 2-8 parts of quaternized zinc-based metal-organic framework material, 0.8-3.6 parts of modified nanometer molybdenum disulfide powder, 0.5-1.7 parts of carboxylated carbon nanotube, 1-2 parts of polyvinylpyrrolidone, 0.5-0.7 parts of polyethylene glycol, 2-4 parts of crosslinking agent, 0.3-0.5 parts of sodium dodecyl sulfate and 80-85 parts of N, N-dimethylacetamide;

[0008] The carboxyl-containing fluorine polyarylether sulfone material is prepared by the following steps:

[0009] The bisphenol AF, 4, 4'-difluorodiphenyl sulfone, phenolphthalin, anhydrous potassium carbonate, dimethylbenzene and cyclobutane sulfone are added into a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube and a reflux condenser, protected by nitrogen, stirred at a temperature of 20-25℃ and a stirring rate of 200-300r / min for 10-20min, then heated to 120-130℃ and stirred for 3-4h, then heated to 160-180℃ and stirred for 5-6h, after the reaction is completed, the reaction product is cooled to room temperature, then poured into deionized water, then adjusted to pH 5-6 with hydrochloric acid solution, then placed, then vacuum filtered, the filter cake is washed with anhydrous ethanol and distilled water for 2-3 times, then placed in a vacuum drying oven and dried at a temperature of 60-70℃ for 10-12h to obtain a carboxyl fluorine-containing polyarylether sulfone material.

[0010] As a preferred embodiment of the present application, the amount ratio of the bisphenol AF, 4, 4'-difluorodiphenyl sulfone, phenolphthalin, anhydrous potassium carbonate, dimethylbenzene and cyclobutane sulfone is 10mmol:20mmol:10mmol:25-30mmol:20-25mL:50-55mL; and the mass fraction of the hydrochloric acid solution is 10-15%.

[0011] As a preferred embodiment of the present application, the quaternary ammonium zinc-based metal-organic framework material is prepared by the following steps:

[0012] Step A1: The 2-bromomethyl dimethyl terephthalate, trimethylamine solution and anhydrous acetonitrile are added into a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube and a reflux condenser, protected by nitrogen, stirred at a temperature of 20-25℃ and a stirring rate of 200-300r / min for 20-30min, then heated to reflux and stirred for 20-30h, after the reaction is completed, the reaction product is cooled to room temperature, then the solvent is removed by rotary evaporation, then purified by silica gel column chromatography with a mixed solvent to obtain a quaternary ammonium dimethyl terephthalate compound;

[0013] Step A2: quaternary ammonium terephthalic acid dimethyl ester compound, sodium hydroxide solution, anhydrous methanol and anhydrous tetrahydrofuran are added to a three-necked flask equipped with a stirrer and a thermometer, stirred at a temperature of 20-25℃ and a stirring rate of 200-300r / min for 3-5min, then heated to 100-110℃ and continued to stir for 10-12h, after the reaction is completed, the reaction product is cooled to room temperature, then rotary evaporation is performed to remove the solvent, then poured into distilled water, then adjusted to pH 2-3 with hydrochloric acid solution, then vacuum filtration, and the filter cake is placed in a vacuum drying oven and dried at a temperature of 40-45℃ for 3-5h to obtain a quaternary ammonium terephthalic acid compound;

[0014] Step A3: quaternary ammonium terephthalic acid compound, zinc nitrate, hydrochloric acid solution and N,N-dimethylformamide are added to a three-necked flask equipped with a stirrer and a thermometer, stirred at a temperature of 20-25℃ and a stirring rate of 200-300r / min for 10-20min, then heated to 90-100℃ and continued to stir for 24-48h, after the reaction is completed, the reaction product is cooled to room temperature, then centrifuged, the precipitate is soaked in anhydrous methanol for 24-48h, then centrifuged, and the precipitate is placed in a vacuum drying oven and dried at a temperature of 40-45℃ for 6-8h to obtain a quaternary ammonium zinc-based metal-organic framework material.

[0015] As a preferred embodiment of the present application, the amount ratio of the 2-bromomethyl terephthalic acid dimethyl ester, trimethylamine solution and anhydrous acetonitrile in step A1 is 5g:25-30mL:40-50mL.

[0016] As a preferred embodiment of the present application, the mass fraction of the trimethylamine solution in step A1 is 30-33%; and the mixed solvent is a mixture of dichloromethane and anhydrous methanol in a volume ratio of 10-12:1.

[0017] As a preferred embodiment of the present application, the amount ratio of the quaternary ammonium terephthalic acid dimethyl ester compound, sodium hydroxide solution, anhydrous methanol and anhydrous tetrahydrofuran in step A2 is 3g:30-40mL:20-30mL:10-15mL.

[0018] As a preferred embodiment of the present application, the molar concentration of the sodium hydroxide solution in step A2 is 3-5mol / L; and the mass fraction of the hydrochloric acid solution is 25-30%.

[0019] As a preferred embodiment of the present application, the amount ratio of the quaternary ammonium terephthalic compound, zinc nitrate, hydrochloric acid solution and N,N-dimethylformamide in step A3 is 10 mmol: 10 mmol: 20-25 mL: 50-60 mL.

[0020] As a preferred embodiment of the present application, the mass fraction of the hydrochloric acid solution in step A3 is 30-35%.

[0021] As a preferred embodiment of the present application, the modified nano-molybdenum disulfide powder is prepared by the following steps:

[0022] The nano-molybdenum disulfide powder, polyvinylpyrrolidone and deionized water are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonic treatment is performed at an ultrasonic frequency of 40-50 kHz for 20-30 min, followed by stirring at a temperature of 20-25℃ and a stirring rate of 200-300 r / min for 10-20 min, then pyrrole and ferric chloride are added and the temperature is raised to 40-45℃, and the reaction is continued for 3-5 h, after which the reaction product is cooled to room temperature, followed by centrifugation, and the precipitate is washed with ethanol solution for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 60-70℃ for 3-5 h to obtain the modified nano-molybdenum disulfide powder.

[0023] As a preferred embodiment of the present application, the amount ratio of the nano-molybdenum disulfide powder, polyvinylpyrrolidone, deionized water, pyrrole and ferric chloride is 3 g: 0.04-0.08 g: 50-55 mL: 0.6-1.2 g: 3-5 g.

[0024] As a preferred embodiment of the present application, the average particle size of the nano-molybdenum disulfide powder is 200 nm; the polyvinylpyrrolidone is PVP-K30; and the volume fraction of the ethanol solution is 40-50%.

[0025] In a second aspect, the present application provides a preparation method of a seawater corrosion-resistant ultrafiltration membrane for water treatment, comprising the following steps:

[0026] Step one: carboxyl fluorine-containing polyarylether sulfone material 17-25 parts, quaternary ammonium zinc-based metal-organic framework material 2-8 parts, modified nano-molybdenum disulfide powder 0.8-3.6 parts, carboxylated carbon nanotube 0.5-1.7 parts, polyvinylpyrrolidone 1-2 parts, polyethylene glycol 0.5-0.7 parts, crosslinking agent 2-4 parts, sodium dodecyl sulfate 0.3-0.5 parts and N,N-dimethylacetamide 80-85 parts are weighed according to weight parts for standby;

[0027] Step two: carboxyl fluorine-containing polyarylene ether sulfone material, quaternary ammonium zinc-based metal organic framework material, modified nanometer molybdenum disulfide powder, carboxylated carbon nanotube, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate and N, N-dimethylacetamide are added into a mixer, stirred and mixed at a temperature of 20-25℃ and a stirring speed of 500-700r / min for 20-30min, then continue to stir and mix at a temperature of 70-80℃ for 5-6h, then stand for 2-4h, then pour onto a smooth glass plate, scrape into a film with a thickness of 100-500μm using a film scraper, then stand for 2-3min, then soak in deionized water for 24-72h, to obtain a seawater corrosion-resistant ultrafiltration membrane for water treatment.

[0028] As a preferred embodiment of the application, the carboxylated carbon nanotube is high-purity multi-walled carbon nanotube TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; and the crosslinking agent is silane coupling agent KH-560.

[0029] Compared with the prior art, the application has the following beneficial effects:

[0030] A seawater corrosion-resistant ultrafiltration membrane for water treatment and a preparation method thereof, wherein carboxyl fluorine-containing polyarylene ether sulfone material, quaternary ammonium zinc-based metal organic framework material, modified nanometer molybdenum disulfide powder, carboxylated carbon nanotube, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate and N, N-dimethylacetamide are stirred and mixed, then scraped into a film, to obtain a seawater corrosion-resistant ultrafiltration membrane for water treatment; the ultrafiltration membrane uses carboxyl fluorine-containing polyarylene ether sulfone material as the main raw material, so that the ultrafiltration membrane has good chemical stability and corrosion resistance in seawater environment, can effectively resist the corrosion of chlorine ions, salt and other substances in seawater, prolongs the service life of the ultrafiltration membrane, adds quaternary ammonium zinc-based metal organic framework material to the ultrafiltration membrane and uses the porous structure of the material to make the ultrafiltration membrane have higher permeability, thereby improving the removal performance of the ultrafiltration membrane, and also endows the ultrafiltration membrane with excellent antibacterial performance, effectively inhibits the formation of biofilm and avoids biological pollution, thereby reducing the cleaning frequency and operation cost of the ultrafiltration membrane; the addition of modified nanometer molybdenum disulfide powder can utilize the unique layered structure of the material, can construct relatively smooth and rigid interlayer nanometer restriction channels on the surface of the film through ordered stacking and self-assembly, can reduce the adhesion of pollutants in wastewater, and also can utilize the excellent photocatalytic ability of the material, can perform photocatalytic degradation on pollutants, endows the ultrafiltration membrane with photocatalytic antibacterial ability, and thereby improves the self-cleaning and anti-pollution ability of the ultrafiltration membrane, long-term ensures the removal performance of the ultrafiltration membrane and improves the water treatment effect.

[0031] In the process of preparing the ultrafiltration membrane, a carboxyl-containing fluorine polyarylether sulfone material is first prepared, bisphenol AF, 4, 4'-difluorodiphenyl sulfone and phenolphthalein are used as monomers for polymerization to form the carboxyl-containing fluorine polyarylether sulfone material; the carboxyl-containing fluorine polyarylether sulfone material contains a large number of fluorine-containing groups in the molecular structure, thereby forming a chemical inert barrier to prevent the penetration of corrosive media and improve the seawater corrosion resistance, and the molecular structure also contains a large number of carboxyl groups which can react with the epoxy groups on the silane coupling agent KH-560 to form a crosslinked network, further improving the seawater corrosion resistance, and a large number of carboxyl groups impart strong hydrophilicity, which can combine with water molecules through hydrogen bonds to form a stable hydration layer, reducing the adsorption of organic matter and microorganisms in seawater.

[0032] In the process of preparing the ultrafiltration membrane, a quaternary ammonium zinc metal organic framework material is also prepared, 2-bromomethyl dimethyl terephthalate and trimethylamine are reacted, the bromine atoms on the 2-bromomethyl dimethyl terephthalate react with the trimethylamine to form quaternary ammonium groups, obtaining quaternary ammonium dimethyl terephthalate compound, then the ester groups on the quaternary ammonium dimethyl terephthalate compound are hydrolyzed to form carboxyl groups, obtaining quaternary ammonium terephthalate compound, then the quaternary ammonium terephthalate compound and zinc nitrate are reacted, the carboxyl groups on the quaternary ammonium terephthalate compound react with zinc ions to form a quaternary ammonium zinc metal organic framework material; the metal organic framework material is a porous material with a crystal structure formed by self-assembly, which can improve the permeability of the ultrafiltration membrane, improve its removal efficiency and effect, and utilize the quaternary ammonium groups and zinc ions thereon to impart excellent antibacterial properties, thereby inhibiting biofilm formation and solving the biological pollution problem of the ultrafiltration membrane in seawater treatment.

[0033] In the process of preparing the ultrafiltration membrane, a modified nanometer molybdenum disulfide powder is also prepared, pyrrole is used as a polymerization monomer to wrap polypyrrole on the surface of the nanometer molybdenum disulfide powder to obtain the modified nanometer molybdenum disulfide powder; the modified nanometer molybdenum disulfide powder can be uniformly dispersed in the ultrafiltration membrane, not only degrading part of the adsorbed organic matter through photocatalysis, but also enhancing the continuity of the hydration layer to impart excellent anti-pollution performance, and the polypyrrole also has excellent photocatalytic effect, which can further improve the anti-pollution performance, and the modified nanometer molybdenum disulfide powder and the carboxylated carbon nanotube form a "tube-sheet heterostructure", shortening the water molecule path, improving the permeability of the ultrafiltration membrane, and improving the removal performance of the ultrafiltration membrane, and the carboxylated carbon nanotube can form hydrogen bond crosslinking with the carboxyl-containing fluorine polyarylether sulfone material and react with the epoxy groups on the silane coupling agent KH-560 to form a crosslinked network, inhibiting interface defects. BRIEF DESCRIPTION OF DRAWINGS

[0034] In order to facilitate the understanding of those skilled in the art, the present application will be further described below with reference to the accompanying drawings.

[0035] Figure 1 Mg removal rate of the seawater corrosion resistant ultrafiltration membrane for water treatment of the present application examples 1-3 and comparative examples 1-4 before and after seawater immersion 2+ The removal rate test results are shown in the following table:

[0036] Figure 2 Ca removal rate of the seawater corrosion resistant ultrafiltration membrane for water treatment of the present application examples 1-3 and comparative examples 1-4 before and after seawater immersion 2+ The removal rate test results are shown in the following table:

[0037] Figure 3 SO4 removal rate of the seawater corrosion resistant ultrafiltration membrane for water treatment of the present application examples 1-3 and comparative examples 1-4 before and after seawater immersion 2- The removal rate test results are shown in the following table:

[0038] Figure 4 CI removal rate of the seawater corrosion resistant ultrafiltration membrane for water treatment of the present application examples 1-3 and comparative examples 1-4 before and after seawater immersion - The removal rate test results are shown in the following table:

[0039] Figure 5 The E. coli antibacterial rate test results of the seawater corrosion resistant ultrafiltration membrane for water treatment of the present application examples 1-3 and comparative examples 1-4 before and after seawater immersion are shown in the following table:

[0040] Figure 6 The S. aureus antibacterial rate test results of the seawater corrosion resistant ultrafiltration membrane for water treatment of the present application examples 1-3 and comparative examples 1-4 before and after seawater immersion are shown in the following table. DETAILED DESCRIPTION

[0041] In order to make the personnel in the technical field better understand the present application scheme, the technical scheme in the present application examples will be described clearly and completely below in combination with the drawings in the present application examples. Obviously, the described examples are only some of the present application examples, not all. Based on the examples in the present application, all other examples obtained by the person skilled in the art without creative labor are within the scope of the present application.

[0042] Example 1:

[0043] The present embodiment is a preparation method of a seawater corrosion resistant ultrafiltration membrane for water treatment, comprising the following steps:

[0044] Step S1: 10 mmol of bisphenol AF, 20 mmol of 4,4'-difluorodiphenyl sulfone, 10 mmol of phenolphthalin, 25 mmol of anhydrous potassium carbonate, 20 mL of dimethylbenzene, and 50 mL of cyclobutan sulfone were added to a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube, and a reflux condenser, and protected by nitrogen, and stirred at 20°C and 200 r / min for 10 min, then heated to 120°C and stirred for 3 h, then heated to 160°C and stirred for 5 h, and after the reaction was completed, the reaction product was cooled to room temperature, then poured into deionized water, then adjusted to pH 6 with a 10% hydrochloric acid solution, then allowed to stand, then vacuum filtered, and the filter cake was washed twice with anhydrous ethanol and distilled water, then placed in a vacuum drying oven and dried at 60°C for 10 h to obtain a carboxyl fluorine-containing polyarylether sulfone material;

[0045] Step S2: 5 g of 2-bromomethyl dimethyl terephthalate, 25 mL of a 30% trimethylamine solution, and 40 mL of anhydrous acetonitrile were added to a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube, and a reflux condenser, and protected by nitrogen, and stirred at 20°C and 200 r / min for 20 min, then heated to reflux and stirred for 20 h, and after the reaction was completed, the reaction product was cooled to room temperature, then rotary evaporated to remove the solvent, then purified by silica gel column chromatography with a mixed solvent of dichloromethane and anhydrous methanol in a volume ratio of 10:1 to obtain a quaternary ammonium terephthalate dimethyl ester compound;

[0046] Step S3: 3 g of the quaternary ammonium terephthalate dimethyl ester compound, 30 mL of a 3 mol / L sodium hydroxide solution, 20 mL of anhydrous methanol, and 10 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred at 20°C and 200 r / min for 3 min, then heated to 100°C and stirred for 10 h, and after the reaction was completed, the reaction product was cooled to room temperature, then rotary evaporated to remove the solvent, then poured into distilled water, then adjusted to pH 3 with a 25% hydrochloric acid solution, then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at 40°C for 3 h to obtain a quaternary ammonium terephthalate compound;

[0047] Step S4: 10 mmol of quaternary ammonium terephthalic acid compound, 10 mmol of zinc nitrate, 20 mL of 30% hydrochloric acid solution, and 50 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred at 20°C and 200 r / min for 10 min, then the temperature was raised to 90°C and the reaction was continued for 24 h. After the reaction was completed, the reaction product was cooled to room temperature, then centrifuged, and the precipitate was soaked in anhydrous methanol for 24 h, then centrifuged, and the precipitate was placed in a vacuum drying oven and dried at 40°C for 6 h to obtain a quaternary ammonium zinc-based metal-organic framework material;

[0048] Step S5: 3 g of nano-molybdenum disulfide powder with an average particle size of 200 nm, 0.04 g of polyvinylpyrrolidone PVP-K30, and 50 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically treated at an ultrasonic frequency of 40 kHz for 20 min, then stirred at 20°C and 200 r / min for 10 min, then 0.6 g of pyrrole, 3 g of ferric chloride were added and the temperature was raised to 40°C and the reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, then centrifuged, and the precipitate was washed with 40% ethanol solution twice, then placed in a vacuum drying oven and dried at 60°C for 3 h to obtain modified nano-molybdenum disulfide powder;

[0049] Step S6: carboxyl-containing fluorine-containing polyarylether sulfone material 17 parts, quaternary ammonium zinc-based metal-organic framework material 2 parts, modified nano-molybdenum disulfide powder 0.8 parts, carboxylated carbon nanotube 0.5 parts, polyvinylpyrrolidone 1 part, polyethylene glycol 0.5 parts, crosslinking agent 2 parts, sodium dodecyl sulfate 0.3 parts, and N,N-dimethylacetamide 80 parts were weighed according to weight parts, and were prepared for use. The carboxylated carbon nanotube is high-purity multi-walled carbon nanotube TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; and the crosslinking agent is silane coupling agent KH-560;

[0050] Step S7: The carboxyl-containing fluorine-containing polyarylether sulfone material, the quaternary ammonium zinc-based metal-organic framework material, the modified nano-molybdenum disulfide powder, the carboxylated carbon nanotube, the polyvinylpyrrolidone, the polyethylene glycol, the crosslinking agent, the sodium dodecyl sulfate, and the N,N-dimethylacetamide were added to a mixer and stirred and mixed at 20°C and 500 r / min for 20 min, then the temperature was raised to 70°C and the stirring and mixing was continued for 5 h, then it was left to stand for 2 h, then it was poured onto a smooth glass plate and scraped with a film scraper to form a film with a thickness of 200 μm, then it was left to stand for 2 min, then it was soaked in deionized water for 24 h to obtain a seawater corrosion-resistant ultrafiltration membrane for water treatment.

[0051] Embodiment 2:

[0052] The embodiment is a preparation method of a seawater corrosion resistant ultrafiltration membrane for water treatment, comprising the following steps:

[0053] Step S1: 10 mmol of bisphenol AF, 20 mmol of 4,4'-difluorodiphenyl sulfone, 10 mmol of phenolphthalein, 28 mmol of anhydrous potassium carbonate, 22 mL of dimethylbenzene and 52 mL of cyclobutane sulfone are added into a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube and a reflux condenser, nitrogen is introduced for protection, stirring is carried out at a temperature of 22°C and a stirring speed of 250 r / min for 15 min, then the temperature is increased to 125°C, and stirring is continued for 3.5 h, then the temperature is increased to 170°C, and stirring is continued for 5.5 h, after the reaction is completed, the reaction product is cooled to room temperature, then it is poured into deionized water, then a hydrochloric acid solution with a mass fraction of 12% is used to adjust the pH to 5.5, then it is left to stand, then vacuum filtration is carried out, the filter cake is washed with anhydrous ethanol and distilled water in sequence for two times, then it is placed in a vacuum drying box, and dried at a temperature of 65°C for 11 h, thereby obtaining a carboxyl fluorine-containing polyarylether sulfone material;

[0054] Step S2: 5 g of 2-bromomethyl dimethyl terephthalate, 28 mL of a trimethylamine solution with a mass fraction of 32% and 45 mL of anhydrous acetonitrile are added into a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube and a reflux condenser, nitrogen is introduced for protection, stirring is carried out at a temperature of 22°C and a stirring speed of 250 r / min for 25 min, then the temperature is increased to reflux, and stirring is continued for 25 h, after the reaction is completed, the reaction product is cooled to room temperature, then the solvent is removed by rotary evaporation, then a mixed solvent prepared by mixing dichloromethane, anhydrous methanol in a volume ratio of 11:1 is used for silica gel column chromatography purification, thereby obtaining a quaternary ammonium terephthalate dimethyl ester compound;

[0055] Step S3: 3 g of the quaternary ammonium terephthalate dimethyl ester compound, 35 mL of a sodium hydroxide solution with a molar concentration of 4 mol / L, 25 mL of anhydrous methanol and 12 mL of anhydrous tetrahydrofuran are added into a three-necked flask equipped with a stirrer and a thermometer, stirring is carried out at a temperature of 22°C and a stirring speed of 250 r / min for 4 min, then the temperature is increased to 105°C, and stirring is continued for 11 h, after the reaction is completed, the reaction product is cooled to room temperature, then the solvent is removed by rotary evaporation, then it is poured into distilled water, then a hydrochloric acid solution with a mass fraction of 28% is used to adjust the pH to 2.5, then vacuum filtration is carried out, and the filter cake is placed in a vacuum drying box and dried at a temperature of 42°C for 4 h, thereby obtaining a quaternary ammonium terephthalate compound;

[0056] Step S4: 10 mmol of quaternary ammonium terephthalic acid compound, 10 mmol of zinc nitrate, 22 mL of 32% hydrochloric acid solution, and 55 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred at 22°C and 250 r / min for 15 min, then the temperature was raised to 95°C and the reaction was continued for 36 h. After the reaction was completed, the reaction product was cooled to room temperature, then centrifuged, and the precipitate was soaked in anhydrous methanol for 36 h, then centrifuged, and the precipitate was placed in a vacuum drying oven and dried at 42°C for 7 h to obtain a quaternary ammonium zinc-based metal-organic framework material;

[0057] Step S5: 3 g of nano-molybdenum disulfide powder with an average particle size of 200 nm, 0.06 g of polyvinylpyrrolidone PVP-K30, and 52 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically treated at an ultrasonic frequency of 45 kHz for 25 min, then stirred at 22°C and 250 r / min for 15 min, then 0.9 g of pyrrole, 4 g of ferric chloride were added and the temperature was raised to 42°C and the reaction was continued for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, then centrifuged, and the precipitate was washed with 45% ethanol solution twice, then placed in a vacuum drying oven and dried at 65°C for 4 h to obtain modified nano-molybdenum disulfide powder;

[0058] Step S6: carboxyl-containing fluorine-containing polyarylether sulfone material 21 parts, quaternary ammonium zinc-based metal-organic framework material 5 parts, modified nano-molybdenum disulfide powder 2.2 parts, carboxylated carbon nanotube 1.1 parts, polyvinylpyrrolidone 1.5 parts, polyethylene glycol 0.6 parts, crosslinking agent 3 parts, sodium dodecyl sulfate 0.4 parts, and N,N-dimethylacetamide 82 parts were weighed according to weight parts, and were prepared for use. The carboxylated carbon nanotube is high-purity multi-walled carbon nanotube TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; and the crosslinking agent is silane coupling agent KH-560;

[0059] Step S7: The carboxyl-containing fluorine-containing polyarylether sulfone material, the quaternary ammonium zinc-based metal-organic framework material, the modified nano-molybdenum disulfide powder, the carboxylated carbon nanotube, the polyvinylpyrrolidone, the polyethylene glycol, the crosslinking agent, the sodium dodecyl sulfate, and the N,N-dimethylacetamide were added to a mixer and stirred and mixed at 22°C and 600 r / min for 25 min, then the temperature was raised to 75°C and the stirring and mixing was continued for 5.5 h, then it was left to stand for 3 h, then it was poured onto a smooth glass plate and scraped with a film scraper to form a film with a thickness of 200 μm, then it was left to stand for 2.5 min, then it was soaked in deionized water for 48 h to obtain a seawater corrosion-resistant ultrafiltration membrane for water treatment.

[0060] Example 3:

[0061] The embodiment is a preparation method of a seawater corrosion resistant ultrafiltration membrane for water treatment, comprising the following steps:

[0062] Step S1: 10 mmol of bisphenol AF, 20 mmol of 4,4'-difluorodiphenyl sulfone, 10 mmol of phenolphthalein, 30 mmol of anhydrous potassium carbonate, 25 mL of dimethylbenzene, and 55 mL of cyclobutane sulfone are added to a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube, and a reflux condenser, nitrogen is introduced for protection, stirring is carried out at a temperature of 25°C and a stirring rate of 300 r / min for 20 min, then the temperature is raised to 130°C, and stirring is continued for 4 h, then the temperature is raised to 180°C, and stirring is continued for 6 h, after the reaction is completed, the reaction product is cooled to room temperature, then it is poured into deionized water, then a 15% hydrochloric acid solution is used to adjust the pH to 5, then it is left to stand, then vacuum filtration is carried out, the filter cake is washed with anhydrous ethanol and distilled water three times in sequence, then it is placed in a vacuum drying oven, and dried at a temperature of 70°C for 12 h, to obtain a carboxyl fluorine-containing polyarylether sulfone material;

[0063] Step S2: 5 g of 2-bromomethyl dimethyl terephthalate, 30 mL of a 33% trimethylamine solution, and 50 mL of anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube, and a reflux condenser, nitrogen is introduced for protection, stirring is carried out at a temperature of 25°C and a stirring rate of 300 r / min for 30 min, then the temperature is raised to reflux, and stirring is continued for 30 h, after the reaction is completed, the reaction product is cooled to room temperature, then the solvent is removed by rotary evaporation, then a mixed solvent of dichloromethane and anhydrous methanol in a volume ratio of 12:1 is used for silica gel column chromatography purification, to obtain a quaternary ammonium terephthalate dimethyl ester compound;

[0064] Step S3: 3 g of the quaternary ammonium terephthalate dimethyl ester compound, 40 mL of a 5 mol / L sodium hydroxide solution, 30 mL of anhydrous methanol, and 15 mL of anhydrous tetrahydrofuran are added to a three-necked flask equipped with a stirrer and a thermometer, stirring is carried out at a temperature of 25°C and a stirring rate of 300 r / min for 5 min, then the temperature is raised to 110°C, and stirring is continued for 12 h, after the reaction is completed, the reaction product is cooled to room temperature, then the solvent is removed by rotary evaporation, then it is poured into distilled water, then a 30% hydrochloric acid solution is used to adjust the pH to 2, then vacuum filtration is carried out, and the filter cake is placed in a vacuum drying oven and dried at a temperature of 45°C for 5 h, to obtain a quaternary ammonium terephthalate compound;

[0065] Step S4: 10 mmol of quaternary ammonium terephthalic acid compound, 10 mmol of zinc nitrate, 25 mL of 35% hydrochloric acid solution, and 60 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred at 25°C and 300 r / min for 20 min, then the temperature was raised to 100°C and the stirring was continued for 48 h. After the reaction was completed, the reaction product was cooled to room temperature, then centrifuged, and the precipitate was soaked in anhydrous methanol for 48 h, then centrifuged, and the precipitate was placed in a vacuum drying oven and dried at 45°C for 8 h to obtain a quaternary ammonium zinc-based metal-organic framework material;

[0066] Step S5: 3 g of nano-molybdenum disulfide powder with an average particle size of 200 nm, 0.08 g of polyvinylpyrrolidone PVP-K30, and 55 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically treated at an ultrasonic frequency of 50 kHz for 30 min, then stirred at 25°C and 300 r / min for 20 min, then 1.2 g of pyrrole, 5 g of ferric chloride were added and the temperature was raised to 45°C and the stirring was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, then centrifuged, and the precipitate was washed with 50% ethanol solution for 3 times, then placed in a vacuum drying oven and dried at 70°C for 5 h to obtain modified nano-molybdenum disulfide powder;

[0067] Step S6: carboxyl-containing fluorine-containing polyarylether sulfone material 25 parts, quaternary ammonium zinc-based metal-organic framework material 8 parts, modified nano-molybdenum disulfide powder 3.6 parts, carboxylated carbon nanotube 1.7 parts, polyvinylpyrrolidone 2 parts, polyethylene glycol 0.7 parts, crosslinking agent 4 parts, sodium dodecyl sulfate 0.5 parts, and N,N-dimethylacetamide 85 parts were weighed according to weight parts, and were prepared for use. The carboxylated carbon nanotube is high-purity multi-walled carbon nanotube TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; and the crosslinking agent is silane coupling agent KH-560;

[0068] Step S7: The carboxyl-containing fluorine-containing polyarylether sulfone material, the quaternary ammonium zinc-based metal-organic framework material, the modified nano-molybdenum disulfide powder, the carboxylated carbon nanotube, the polyvinylpyrrolidone, the polyethylene glycol, the crosslinking agent, the sodium dodecyl sulfate, and the N,N-dimethylacetamide were added to a mixer and stirred and mixed at 25°C and 700 r / min for 30 min, then the temperature was raised to 80°C and the stirring and mixing was continued for 6 h, then it was left to stand for 4 h, then it was poured onto a smooth glass plate and scraped with a film scraper to form a film with a thickness of 200 μm, then it was left to stand for 3 min, then it was soaked in deionized water for 72 h to obtain a seawater corrosion-resistant ultrafiltration membrane for water treatment.

[0069] Comparative Example 1

[0070] The present comparative example is a preparation method of a seawater corrosion resistant ultrafiltration membrane for water treatment, comprising the following steps:

[0071] Step S1: 10 mmol of bisphenol AF, 20 mmol of 4,4'-difluorodiphenyl sulfone, 10 mmol of phenolphthalein, 30 mmol of anhydrous potassium carbonate, 25 mL of dimethylbenzene, and 55 mL of cyclobutane sulfone were added to a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube, and a reflux condenser, nitrogen was introduced for protection, stirring was carried out at a temperature of 25°C and a stirring rate of 300 r / min for 20 min, then the temperature was raised to 130°C and stirring was continued for 4 h, then the temperature was raised to 180°C and stirring was continued for 6 h, after the reaction was completed, the reaction product was cooled to room temperature, then poured into deionized water, then adjusted to pH 5 with a 15% mass fraction hydrochloric acid solution, then stood, then vacuum filtration, the filter cake was washed with anhydrous ethanol and distilled water three times in turn, then placed in a vacuum drying oven and dried at a temperature of 70°C for 12 h, to obtain a carboxyl fluorine-containing polyarylether sulfone material;

[0072] Step S2: the carboxyl fluorine-containing polyarylether sulfone material 25 parts, carboxylated carbon nanotubes 1.7 parts, polyvinylpyrrolidone 2 parts, polyethylene glycol 0.7 parts, crosslinking agent 4 parts, sodium dodecyl sulfate 0.5 parts, and N,N-dimethylacetamide 85 parts were weighed according to weight parts, for standby; the carboxylated carbon nanotubes are high-purity multi-walled carbon nanotubes TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; the crosslinking agent is silane coupling agent KH-560;

[0073] Step S3: the carboxyl fluorine-containing polyarylether sulfone material, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide were added to a mixer, stirred and mixed at a temperature of 25°C and a stirring rate of 700 r / min for 30 min, then the temperature was raised to 80°C and stirring and mixing was continued for 6 h, then stood for 4 h, then poured onto a smooth glass plate, scraped into a film with a thickness of 200 μm using a film scraper, then stood for 3 min, then soaked in deionized water for 72 h, to obtain a seawater corrosion resistant ultrafiltration membrane for water treatment.

[0074] Comparative Example 2

[0075] The present comparative example is a preparation method of a seawater corrosion resistant ultrafiltration membrane for water treatment, comprising the following steps:

[0076] Step S1: 10 mmol of bisphenol AF, 20 mmol of 4,4'-difluorodiphenyl sulfone, 10 mmol of phenolphthalin, 30 mmol of anhydrous potassium carbonate, 25 mL of dimethylbenzene, and 55 mL of cyclobutan sulfone were added to a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube, and a reflux condenser, and protected by nitrogen, and stirred at 25°C and 300 r / min for 20 min, then heated to 130°C and stirred for 4 h, then heated to 180°C and stirred for 6 h, and after the reaction was completed, the reaction product was cooled to room temperature, then poured into deionized water, then adjusted to pH 5 with a 15% hydrochloric acid solution, then allowed to stand, then vacuum filtered, and the filter cake was washed with anhydrous ethanol and distilled water three times, then placed in a vacuum drying oven and dried at 70°C for 12 h to obtain a carboxyl fluorine-containing polyarylether sulfone material;

[0077] Step S2: 5 g of 2-bromomethyl dimethyl terephthalate, 30 mL of a 33% trimethylamine solution, and 50 mL of anhydrous acetonitrile were added to a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube, and a reflux condenser, and protected by nitrogen, and stirred at 25°C and 300 r / min for 30 min, then heated to reflux and stirred for 30 h, and after the reaction was completed, the reaction product was cooled to room temperature, then rotary evaporated to remove the solvent, then purified by silica gel column chromatography with a mixed solvent of dichloromethane and anhydrous methanol in a volume ratio of 12:1 to obtain a quaternary ammonium terephthalate dimethyl ester compound;

[0078] Step S3: 3 g of the quaternary ammonium terephthalate dimethyl ester compound, 40 mL of a 5 mol / L sodium hydroxide solution, 30 mL of anhydrous methanol, and 15 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred at 25°C and 300 r / min for 5 min, then heated to 110°C and stirred for 12 h, and after the reaction was completed, the reaction product was cooled to room temperature, then rotary evaporated to remove the solvent, then poured into distilled water, then adjusted to pH 2 with a 30% hydrochloric acid solution, then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at 45°C for 5 h to obtain a quaternary ammonium terephthalate compound;

[0079] Step S4: 10 mmol of quaternary ammonium terephthalic acid compound, 10 mmol of zinc nitrate, 25 mL of 35% hydrochloric acid solution, and 60 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred at a temperature of 25°C and a stirring rate of 300 r / min for 20 min, and then the temperature was raised to 100°C and the stirring was continued for 48 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was soaked in anhydrous methanol for 48 h, and then centrifuged. The precipitate was placed in a vacuum drying oven and dried at a temperature of 45°C for 8 h to obtain a quaternary ammonium zinc-based metal-organic framework material;

[0080] Step S5: 25 parts of carboxyl-containing fluorine-containing polyarylether sulfone material, 1.7 parts of carboxylated carbon nanotube, 8 parts of quaternary ammonium zinc-based metal-organic framework material, 2 parts of polyvinylpyrrolidone, 0.7 parts of polyethylene glycol, 4 parts of crosslinking agent, 0.5 parts of sodium dodecyl sulfate, and 85 parts of N,N-dimethylacetamide were weighed according to the weight parts, and were prepared for use. The carboxylated carbon nanotube was high-purity multi-walled carbon nanotube TNMC1. The polyvinylpyrrolidone was PVP-K30. The polyethylene glycol was PEG-6000. The crosslinking agent was silane coupling agent KH-560.

[0081] Step S6: The carboxyl-containing fluorine-containing polyarylether sulfone material, the quaternary ammonium zinc-based metal-organic framework material, the carboxylated carbon nanotube, the polyvinylpyrrolidone, the polyethylene glycol, the crosslinking agent, the sodium dodecyl sulfate, and the N,N-dimethylacetamide were added to a mixer and stirred at a temperature of 25°C and a stirring rate of 700 r / min for 30 min, and then the temperature was raised to 80°C and the stirring was continued for 6 h. After standing for 4 h, the mixture was poured onto a smooth glass plate and scraped with a film scraper to form a film with a thickness of 200 μm. After standing for 3 min, the film was soaked in deionized water for 72 h to obtain a seawater corrosion-resistant ultrafiltration membrane for water treatment.

[0082] Comparative Example 3:

[0083] This comparative example is a method for preparing a seawater corrosion-resistant ultrafiltration membrane for water treatment, comprising the following steps:

[0084] Step S1: 10 mmol of bisphenol AF, 20 mmol of 4,4'-difluorodiphenyl sulfone, 10 mmol of phenolphthaline, 30 mmol of anhydrous potassium carbonate, 25 mL of dimethylbenzene and 55 mL of cyclobutan sulfone were added into a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube and a reflux condenser, nitrogen was introduced for protection, stirring was carried out at a temperature of 25℃ and a stirring speed of 300 r / min for 20 min, then the temperature was increased to 130℃ and the reaction was continued for 4 h, then the temperature was increased to 180℃ and the reaction was continued for 6 h, after the reaction was completed, the reaction product was cooled to room temperature, then it was poured into deionized water, then a 15% hydrochloric acid solution was used to adjust the pH to 5, then it was left to stand, then vacuum filtration was carried out, the filter cake was washed with anhydrous ethanol and distilled water for 3 times, then it was placed in a vacuum drying oven and dried at a temperature of 70℃ for 12 h, thereby obtaining a carboxyl fluorine-containing polyarylether sulfone material;

[0085] Step S2: 3 g of nano molybdenum disulfide powder with an average particle size of 200 nm, 0.08 g of polyvinylpyrrolidone PVP-K30 and 55 mL of deionized water were added into a three-necked flask equipped with a stirrer and a thermometer, ultrasonic treatment was carried out at an ultrasonic frequency of 50 kHz for 30 min, then stirring was carried out at a temperature of 25℃ and a stirring speed of 300 r / min for 20 min, then 1.2 g of pyrrole, 5 g of ferric chloride were added and the reaction was continued under the condition of increasing the temperature to 45℃ for 5 h, after the reaction was completed, the reaction product was cooled to room temperature, then centrifugation was carried out, the precipitate was washed with a 50% ethanol solution for 3 times, then it was placed in a vacuum drying oven and dried at a temperature of 70℃ for 5 h, thereby obtaining a modified nano molybdenum disulfide powder;

[0086] Step S3: carboxyl fluorine-containing polyarylether sulfone material 25 parts, modified nano molybdenum disulfide powder 3.6 parts, carboxylated carbon nanotube 1.7 parts, polyvinylpyrrolidone 2 parts, polyethylene glycol 0.7 parts, crosslinking agent 4 parts, sodium dodecyl sulfate 0.5 parts and N,N-dimethylacetamide 85 parts were weighed according to weight parts, for standby use; the carboxylated carbon nanotube was high-purity multi-walled carbon nanotube TNMC1; the polyvinylpyrrolidone was PVP-K30; the polyethylene glycol was PEG-6000; the crosslinking agent was silane coupling agent KH-560;

[0087] Step S4: the carboxyl fluorine-containing polyarylether sulfone material, modified nanometer molybdenum disulfide powder, carboxylated carbon nanotube, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate and N, N-dimethylacetamide were added into a mixer, stirred and mixed at a temperature of 25°C and a stirring rate of 700 r / min for 30 min, then continued to be stirred and mixed at a temperature of 80°C for 6 h, then stood for 4 h, then poured onto a smooth glass plate, scraped into a film with a thickness of 200 μm by a film scraper, then stood for 3 min, then soaked in deionized water for 72 h, to obtain a seawater corrosion resistant ultrafiltration membrane for water treatment.

[0088] Comparative Example 4:

[0089] The present comparative example is a preparation method of a seawater corrosion resistant ultrafiltration membrane for water treatment, comprising the following steps:

[0090] Step S1: 20 mmol of bisphenol A, 20 mmol of 4, 4'-difluorodiphenyl sulfone, 30 mmol of anhydrous potassium carbonate, 25 mL of dimethylbenzene and 55 mL of cyclobutane sulfone were added into a three-necked flask equipped with a stirrer, a thermometer, a gas inlet tube and a reflux condenser, protected by nitrogen, stirred and reacted at a temperature of 25°C and a stirring rate of 300 r / min for 20 min, then continued to be stirred and reacted at a temperature of 130°C for 4 h, then continued to be stirred and reacted at a temperature of 180°C for 6 h, after the reaction was completed, the reaction product was cooled to room temperature, then poured into deionized water, then adjusted to pH 5 with a 15% mass fraction hydrochloric acid solution, then stood, then vacuum filtered, the filter cake was washed with anhydrous ethanol and distilled water for 3 times in sequence, then placed in a vacuum drying oven, dried at a temperature of 70°C for 12 h, to obtain a polyarylether sulfone material;

[0091] Step S2: 10 mmol of terephthalic acid, 10 mmol of zinc nitrate, 25 mL of a 35% mass fraction hydrochloric acid solution and 60 mL of N, N-dimethylformamide were added into a three-necked flask equipped with a stirrer and a thermometer, stirred and reacted at a temperature of 25°C and a stirring rate of 300 r / min for 20 min, then continued to be stirred and reacted at a temperature of 100°C for 48 h, after the reaction was completed, the reaction product was cooled to room temperature, then centrifuged, the precipitate was added into anhydrous methanol and soaked for 48 h, then centrifuged, the precipitate was placed in a vacuum drying oven and dried at a temperature of 45°C for 8 h, to obtain a zinc-based metal organic framework material;

[0092] Step S3: Weigh out 25 parts by weight of polyarylethersulfone material, 8 parts by weight of zinc-based metal-organic framework material, 3.6 parts by weight of molybdenum disulfide nanopowder, 1.7 parts by weight of carboxylated carbon nanotubes, 2 parts by weight of polyvinylpyrrolidone, 0.7 parts by weight of polyethylene glycol, 4 parts by weight of crosslinking agent, 0.5 parts by weight of sodium dodecyl sulfate, and 85 parts by weight of N,N-dimethylacetamide, and set aside. The average particle size of the molybdenum disulfide nanopowder is 200 nm; the carboxylated carbon nanotubes are high-purity multi-walled carbon nanotubes TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; and the crosslinking agent is silane coupling agent KH-560.

[0093] Step S4: Add polyarylethersulfone material, zinc-based metal-organic framework material, nano-molybdenum disulfide powder, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide to a mixer and stir for 30 minutes at 25°C and 700 r / min. Then, heat to 80°C and continue stirring for 6 hours. After standing for 4 hours, pour the mixture onto a smooth glass plate and scrape it into a membrane with a thickness of 200 μm using a membrane scraper. After standing for 3 minutes, immerse the membrane in deionized water for 72 hours to obtain an ultrafiltration membrane for water treatment that is resistant to seawater corrosion.

[0094] Performance testing

[0095] The seawater corrosion-resistant ultrafiltration membranes for water treatment in Examples 1-3 and Comparative Examples 1-4 were tested for their removal performance and antibacterial performance before and after immersion in seawater for 60 days. The removal performance was measured under operating pressure of 1.0 MPa and a water recovery rate of 30% to determine the Mg content in seawater. 2+ Ca 2+ SO4 2- and CI - The removal rate, test results are as follows Figures 1-4 As shown, the antibacterial performance was tested using the traditional plate count method to determine the antibacterial rate against Escherichia coli and Staphylococcus aureus. The test results are as follows: Figures 5-6 As shown; among them, Mg in seawater 2+ Ca 2+ SO4 2- and CI - The mass concentrations were 1080, 351, 2366 and 15308 mg / L, respectively.

[0096] See Figures 1-6As shown, according to the comparison between examples 1-3 and comparative examples 1-4, it can be known that the use of carboxyl-containing fluorine-containing polyarylene ether sulfone material, and the addition of quaternary ammonium zinc-based metal-organic framework material and modified nanometer molybdenum disulfide powder can significantly improve the removal performance and antibacterial performance of the ultrafiltration membrane, so that the seawater corrosion resistant ultrafiltration membrane for water treatment has excellent removal performance and antibacterial performance.

[0097] In the description of the present specification, the description referring to the terms "one embodiment", "an example", "a specific example" and the like means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0098] The above is only an example and description of the present application, and those skilled in the art can make various modifications or supplements to the described specific embodiments or use similar ways to replace, as long as it does not deviate from the invention or exceed the scope defined in the present application, which shall belong to the protection scope of the present application.

Claims

1. A seawater corrosion resistant ultrafiltration membrane for water treatment, characterized by, The following components are included by weight parts: Carboxyl-containing fluorine polyarylene ether sulfone material 17-25 parts, quaternary ammonium zinc-based metal organic framework material 2-8 parts, modified nanometer molybdenum disulfide powder 0.8-3.6 parts, carboxylated carbon nanotubes 0.5-1.7 parts, polyvinylpyrrolidone 1-2 parts, polyethylene glycol 0.5-0.7 parts, crosslinking agent 2-4 parts, sodium dodecyl sulfate 0.3-0.5 parts, and N,N-dimethylacetamide 80-85 parts; The carboxyl-containing fluorine polyarylene ether sulfone material is prepared by the following steps: The bisphenol AF, 4,4'-difluorodiphenyl sulfone, phenolphthalein, anhydrous potassium carbonate, xylene and sulfolane are stirred and reacted, the reaction product is cooled after the reaction is completed, then poured into deionized water, then the pH is adjusted with a hydrochloric acid solution, then left to stand, then vacuum filtration, the filter cake is washed and dried to obtain the carboxyl-containing fluorine polyarylene ether sulfone material.

2. The seawater corrosion resistant ultrafiltration membrane for water treatment according to claim 1, characterized in that, The amount ratio of the bisphenol AF, 4,4'-difluorodiphenyl sulfone, phenolphthalein, anhydrous potassium carbonate, xylene and sulfolane is 10 mmol:20 mmol:10 mmol:25-30 mmol:20-25 mL:50-55 mL; the mass fraction of the hydrochloric acid solution is 10-15%.

3. The seawater corrosion resistant ultrafiltration membrane for water treatment according to claim 1, characterized in that, The quaternary ammonium zinc-based metal organic framework material is prepared by the following steps: Step A1: 2-bromomethyl dimethyl terephthalate, trimethylamine solution and anhydrous acetonitrile are stirred and reacted, the reaction product is cooled after the reaction is completed, then rotary evaporation, then silica gel column chromatography purification with a mixed solvent to obtain a quaternary ammonium dimethyl terephthalate compound; Step A2: The quaternary ammonium dimethyl terephthalate compound, sodium hydroxide solution, anhydrous methanol and anhydrous tetrahydrofuran are stirred and reacted, the reaction product is cooled after the reaction is completed, then rotary evaporation, then poured into distilled water, then the pH is adjusted with a hydrochloric acid solution, then vacuum filtration, the filter cake is dried to obtain a quaternary ammonium terephthalate compound; Step A3: The quaternary ammonium terephthalate compound, zinc nitrate, hydrochloric acid solution and N,N-dimethylformamide are stirred and reacted, the reaction product is cooled after the reaction is completed, then centrifugation, the precipitate is soaked in anhydrous methanol, then centrifugation, the precipitate is dried to obtain a quaternary ammonium zinc-based metal organic framework material.

4. The seawater corrosion resistant ultrafiltration membrane for water treatment according to claim 3, characterized in that, The amount ratio of the 2-bromomethyl dimethyl terephthalate, trimethylamine solution and anhydrous acetonitrile in step A1 is 5 g:25-30 mL:40-50 mL; the mass fraction of the trimethylamine solution is 30-33%; the mixed solvent is a mixture of dichloromethane, anhydrous methanol in a volume ratio of 10-12:

1.

5. The seawater corrosion resistant ultrafiltration membrane for water treatment according to claim 3, characterized in that, The amount ratio of the quaternary ammonium dimethyl terephthalate compound, sodium hydroxide solution, anhydrous methanol and anhydrous tetrahydrofuran in step A2 is 3 g:30-40 mL:20-30 mL:10-15 mL; the molar concentration of the sodium hydroxide solution is 3-5 mol / L; the mass fraction of the hydrochloric acid solution is 25-30%.

6. The seawater corrosion resistant ultrafiltration membrane for water treatment according to claim 3, characterized in that, The amount ratio of the quaternary ammonium terephthalic compound, zinc nitrate, hydrochloric acid solution and N,N-dimethylformamide in step A3 is 10 mmol:10 mmol:20-25 mL:50-60 mL; the mass fraction of the hydrochloric acid solution is 30-35%.

7. The seawater corrosion resistant ultrafiltration membrane for water treatment according to claim 1, characterized in that, The modified nano molybdenum disulfide powder is prepared by the following steps: The nano molybdenum disulfide powder, polyvinylpyrrolidone and deionized water are ultrasonically treated, then pyrrole and ferric chloride are added for stirring reaction, the reaction product is cooled after the reaction, then centrifuged, and the precipitate is washed and dried to obtain the modified nano molybdenum disulfide powder.

8. The seawater corrosion resistant ultrafiltration membrane for water treatment according to claim 7, characterized in that, The amount ratio of the nano molybdenum disulfide powder, polyvinylpyrrolidone, deionized water, pyrrole and ferric chloride is 3 g:0.04-0.08 g:50-55 mL:0.6-1.2 g:3-5 g; the average particle size of the nano molybdenum disulfide powder is 200 nm; and the polyvinylpyrrolidone is PVP-K30.

9. A method for producing a seawater corrosion resistant ultrafiltration membrane for water treatment according to any one of claims 1 to 8, characterized by, The method comprises the following steps: Step one: carboxyl fluorine-containing polyarylether sulfone material 17-25 parts, quaternary ammonium zinc-based metal organic framework material 2-8 parts, modified nano molybdenum disulfide powder 0.8-3.6 parts, carboxylated carbon nanotube 0.5-1.7 parts, polyvinylpyrrolidone 1-2 parts, polyethylene glycol 0.5-0.7 parts, crosslinking agent 2-4 parts, sodium dodecyl sulfate 0.3-0.5 parts and N,N-dimethylacetamide 80-85 parts are weighed according to weight parts and prepared for use; Step two: the carboxyl fluorine-containing polyarylether sulfone material, quaternary ammonium zinc-based metal organic framework material, modified nano molybdenum disulfide powder, carboxylated carbon nanotube, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate and N,N-dimethylacetamide are added to a mixing machine, stirred and mixed at a temperature of 20-25 DEG C and a stirring speed of 500-700 r / min for 20-30 min, then continuously stirred and mixed at a temperature of 70-80 DEG C for 5-6 h, then left to stand for 2-4 h, then poured onto a smooth glass plate, scraped into a film with a thickness of 100-500 mu m by using a film scraper, then left to stand for 2-3 min, then soaked in deionized water for 24-72 h to obtain a seawater corrosion-resistant ultrafiltration membrane for water treatment.

10. The method of claim 9, wherein the method is characterized by: The carboxylated carbon nanotube is high-purity multi-walled carbon nanotube TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; and the crosslinking agent is silane coupling agent KH-560.

Citation Information

Patent Citations

  • Multi-walled composite conductive carbon nanotube-polyvinylidene fluoride ultrafiltration membrane and preparation method thereof

    CN103785305A

  • Modified PVDF ultra-filtration membrane preparation method with namometer MoS2

    CN104138716A

  • Method for preparing porous zinc oxide microspheres with metal organic skeleton MOF-5 materials being precursors

    CN105271364A

  • TiO2 / fluorine-containing polyether sulphone, preparation method and hybrid ultrafiltration membrane

    CN105694458A

  • Carboxylic carbon nano-tube based high-performance flat-plate type forward osmosis membrane and preparation method thereof

    CN106925138A

Cited By

  • Formula of low-damage high-efficiency cleaning agent for MBR (Membrane Bioreactor)

    CN121648747A